Germinated brown rice (GBR) reduces the incidence of aberrant crypt foci with the involvement of β-catenin and COX-2 in azoxymethane-induced colon cancer in rats. - Saiful Yazan, Latifah; Nurdin, Armania; Tan, Hern Tze; Yaacob, Azhar; Abdul Hadi, Nordiana; Saad, Norazalina; Ithnin, Hairuszah; Moin, Saidi; Ismail, Maznah (BioMed Central, 2010)
Chemoprevention has become an important area in cancer research due to the failure of current therapeutic modalities. Epidemiological and preclinical studies have demonstrated that nutrition plays a vital role in the etiology of cancer. This study was conducted to determine the chemopreventive effects of germinated brown rice (GBR) in rats induced with colon cancer. GBR is brown rice that has been claimed to be richer in nutrients compared to the common white rice. The male Sprague Dawley rats (6 weeks of age) were randomly divided into 5 groups: (G1) positive control (with colon cancer, unfed with GBR), (G2) fed with 2.5 g/kg of GBR (GBR (g)/weight of rat (kg)), (G3) fed with 5 g/kg of GBR, (G4) fed with 10 g/kg of GBR and (G5) negative control (without colon cancer, unfed with GBR). GBR was administered orally once daily via gavage after injection of 15 mg/kg of body weight of azoxymethane (AOM) once a week for two weeks, intraperitonially. After 8 weeks of treatment, animals were sacrificed and colons were removed. Colonic aberrant crypt foci (ACF) were evaluated histopathologically. Total number of ACF and AC, and multicrypt of ACF, and the expression of β-catenin and COX-2 reduced significantly (p < 0.05) in all the groups treated with GBR (G2, G3 and G4) compared to the control group (G1). Spearman rank correlation test showed significant positive linear relationship between total β-catenin and COX-2 score(Spearman's rho = 0.616, p = 0.0001). It is demonstrated that GBRinhibits the development of total number of ACF and AC, and multicrypt of ACF, reduces the expression of β-catenin and COX-2, and thus can be a promising dietary supplement in prevention of colon cancer.